SUPERSUIT - ITS PAST, PRESENT, FUTURE - MALYUGA, Oleg Vladimirovich (Вопросы экологии, 2017)
Throughout our history, a person has always lacked the strength to lift heavy objects, have greater impact strength and endurance. But thanks to science and technology, people were still able to increase their power capabilities. So there were exoskeletons - special costumes that increase human strength through the outer frame. The peculiarity of these devices is their lightness and ability to mechanically repeat all human movements. Agree, this is a great and significant achievement in modern technology, which is used in medicine, military purposes, in places with radiation hazards, construction and industry. With the exoskeleton, the soldier can carry more weapons on him, he is largely protected from enemy bullets, faster and more active in his movements. Since the main forces of the suit takes over, a person saves more energy and, of course, their health. And just think how useful an exoskeleton is in medicine! This is just a godsend for the disabled, who have completely lost faith in the fact that they can walk again, and the paralyzed will be able to move their limbs with the power of thought, being in a special suit.